1993
DOI: 10.1007/bf00225008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a RAPD marker linked to the oat stem rust gene Pg3

Abstract: The feasibility of identifying molecular markers linked to disease resistance genes in oats was investigated utilizing random primers in conjunction with polymerase chain reaction technology. A pair of near-isogenic oat lines were screened for polymorphic DNA fragments linked to the stem rust resistance gene Pg3. Two primers were identified which amplified DNA fragments that were polymorphic between the lines analyzed. One primer (ACOpR-2) was shown to be completely linked to the Pg3 locus; the other primer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 11 publications
2
20
0
1
Order By: Relevance
“…RAPD analysis was based on methods reported by Fennimore et al (1999), Penner et al (1993) and Williams et al (1991). Polymerase chain reaction (PCR) conditions were optimised for repeatable amplification of oat and wild red oat DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RAPD analysis was based on methods reported by Fennimore et al (1999), Penner et al (1993) and Williams et al (1991). Polymerase chain reaction (PCR) conditions were optimised for repeatable amplification of oat and wild red oat DNA.…”
Section: Methodsmentioning
confidence: 99%
“…DNA markers and quantitative trait loci (QTLs) associated with anther culture ability traits have been reported in wheat, barley, maize and rice (Beaumont et al 1995, Murigneux et al 1994, He et al 1998, Yamagishi et al 1998, Manninen 2000, Torp et al 2001, Kwon et al 2002. In hexaploid oats, DNA markers associated with agronomically important traits, such as disease resistance (Penner et al 1993, O'Donoughue et al 1996, Bush and Wise 1998, Jin et al 1998, quality (Holland et al 1997, Kianian et al 2000, Groh et al 2001) and dwarfness (Milach et al 1997) have already been reported. However, markers associated with anther culture traits of oats have not yet been published.…”
Section: Introductionmentioning
confidence: 99%
“…Since the development of PCR-based RAPD markers, in which random fragments of DNA are amplified from DNA samples using short, arbitrary primers [35], several resistance genes have been tagged with RAPD markers [e.g. 24,25,31,36]. The use of near-isogenic lines (NILs) can accelerate the identification of DNA markers tightly linked to genes of interest [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of near-isogenic lines and RAPD analysis was used effectively in tomato (Martin et al 1991), lettuce (Paran et al 1991), oat (Penner et al 1993), common bean (Haley et al 1993) and wheat (Dweikat et al 1994) for the purpose of identifying DNA markers for disease and insect resistance genes. However, markerassisted selection with RAPDs is not always feasible because RAPD markers identified in one population are not always useful for another, and some markers lack reliability.…”
Section: Introductionmentioning
confidence: 99%